Politics and society in contemporary Africa - Chazan, Naomi, 1946-; Lewis, Peter, 1957-; Mortimer, Robert A.; Rothchild, Donald S.; Stedman, Stephen John (Boulder, CO : Lynne Rienner Publishers, 1999)
Recognized as the textbook on African politics, as well as an excellent resource for scholars, Politics and Society in Contemporary Africa analyzes the complexities and diversities of the African continent since independence. The authors provide a basic knowledge of political events; political structures, processes, problems, and trends; political economy; and international relations. Clearly organized charts offer easy access to current political, economic, and social data. This edition includes entirely new chapters on political economy and South Africa, as well as revised discussions of civil society, democratic transitions, decentralization, structural adjustment, and Africa in the world economy. -- Publisher description.
Introduction ---- 1. The Diversity of African Politics: Trends and Approaches ---- PART I. THE STRUCTURES OF POLITICS. 2. State Institutions and the Organization of the Public Arena --- 3. Social Groupings --- 4. Ethnicity, Class, and the State ---- PART II. POLITICAL PROCESS AND POLITICAL CHANGE. 5. Regimes in Independent Africa --- 6. High Politics: The Procedures and Practices of Government --- 7. Deep Politics: Political Response, Protest, and Conflict --- 8. Political Transitions and Patterns of Change ---- PART III. POLITICAL ECONOMY. 9. Coping with Transformation: Approaches to Development --- 10. Coping with Change: Crisis and Attempted Reform ---- PART IV. INTERNATIONAL RELATIONS. 11. Inter-African Relations --- 12. Africa in World Politics ---- PART V. POLITICAL FUTURES. 13. South Africa: The Possibilities and Limits of Transforming State and Society --- 14. Africa in the 21st Century ---- Appendixes.
Includes bibliographical references and index.
Keywords: Since 1960; Diplomatic relations; Economic history; Politics and government; Social conditions; Africa -- Politics and government -- 1960-; Book